1971
DOI: 10.1002/cjce.5450490311
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical interpretation of gas oil conversion data on an x‐sieve catalyst

Abstract: A four parameter model based on the catalyst aging theory of Wojciechowski(5) is applied to experimental conversion data in gas oil cracking. The data extends over a range of cat/oil ratios from 0.094 to 3.0, and run times from 1.25 to 40 minutes. Within this range of conditions the model is applied to data with and without thermal conversion and excellent correlation between experimental results and calculated values is obtained. The technique for fitting data to the model is described in some detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

1971
1971
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 6 publications
0
12
0
2
Order By: Relevance
“…VGO is cracked to gasoline, gas and coke. The rate of consumption of reactant j per unit catalyst volume can be expressed as (Pachovsky and Wojciechowski, 1971):…”
Section: Cracking Reactionsmentioning
confidence: 99%
“…VGO is cracked to gasoline, gas and coke. The rate of consumption of reactant j per unit catalyst volume can be expressed as (Pachovsky and Wojciechowski, 1971):…”
Section: Cracking Reactionsmentioning
confidence: 99%
“…From Table 3 it is readily apparent that for both the 4/10 mesh and 30/60 mesh data the selectivity model adequately describes the data at the 95% confidence level. In previous publications (Pachovsky and Wojciechowski, 1971; Best et al, 1971), it has been shown that the conversion model also adequately describes the conversion data at the 95% confidence level for both the 4/10 mesh and 30/60 mesh catalysts.…”
Section: Discussionmentioning
confidence: 79%
“…For instance, Johnson et al (1957) attempted to describe gas oil cracking as following Wheeler's type I11 selectivity. Subsequently, Campbell and Wojciechowski (1969) and Pachovsky and Wojciechowski (1971) showed that a more complex mechanism is required to describe gas oil cracking and postulated a more complex form of behavior.…”
Section: Scopementioning
confidence: 98%
“…The value of n is assumed to be one for the 21 VGO cracking reactions and zero for all other cracking reactions. M a n u s c r i p t There are two other types of rate equations are available in the literature, which can be written as: 1 (for 3-lump model of Pachovsky and Wojciechowski, 1971) eq. (99) 2…”
Section: Coupling Between Gas-solid Flow Model and Cracking Kinetic Mmentioning
confidence: 99%